Rootstock effects on floral induction in commercial Iranian almond cultivars: Insights from morphophysiological, biochemical, and molecular analyses - Masoud Abedian-Chermahini; Behrouz Shiran; Abdolrahman Mohammadkhani; Habibollah Nourbakhsh (PLoS ONE, 2025)
Orchard productivity in almond trees is strongly influenced by rootstock selection, which plays a key role in floral induction and yield optimization. Although several rootstocks are commonly used in Iran, their comparative effects on floral induction in major commercial cultivars remain poorly understood. This study evaluated five Peach × Almond hybrid rootstocks (GN15, GF677, GN15-M, Shurab2, and Shurab3) grafted with two widely grown Iranian cultivars, Mamaee and Shahrud12, to investigate rootstock–scion interactions. These combinations were chosen based on their commercial importance and regional adaptability. A four-year factorial experiment (2021–2025) was conducted in a completely randomized design. Morphological traits, including flower number, blooming density, and vegetative growth, were measured alongside photosynthetic pigments and endogenous hormone profiles. Additionally, the expression of flowering-related genes was analyzed in leaf and bud tissues. Results revealed that Shurab3 significantly enhanced floral induction in both cultivars, with the Shurab3–Shahrud12 combination producing the highest flower number and bloom density. Shurab3 also outperformed GN15 in promoting flowering in Mamaee, whereas the GN15–Mamaee combination showed the lowest performance. Rootstocks GF677, GN15-M, and Shurab2 exhibited intermediate effects. Shurab3 combinations were further associated with higher chlorophyll content, increased indole-3-acetic acid (IAA), and dynamic patterns of abscisic acid (ABA) and gibberellic acid (GA3). Molecular analyses confirmed upregulation of FLOWERING LOCUS T ( FT ), CONSTANS ( CO ), SUPPRESSOR OF OVEREXPRESSION OF CO 1 ( SOC1 ), LEAFY ( LFY ), and APETALA1 ( AP1 ) in Shurab3–Shahrud12, consistent with observed phenotypic improvements. Overall, these findings indicate that both rootstock and scion selection critically influence reproductive performance. Shurab3 emerges as a promising flower-inducing rootstock, providing practical guidance for optimizing orchard management and enhancing almond productivity under regional climatic conditions.